Strategy to Increase The Company’s Production by Integrating the Craig-Harris Productivity Method and Competitive Positioning Analysis - Mohammad Yahya Alvi Habibillah; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
The production process on CV. SPN is inseparable from a decrease in production, the company experienced a production decline of 70% in 2020 and in 2021, this study aims to determine the level of total productivity in the company and can develop the company's position in the market and build products that are trusted by consumers. this research was conducted using the Craig-Harris productivity method. This method was used to determine total productivity and competitive positioning analysis was used to determine the company's position in a market. The results of the productivity measurement obtained, in 2019 the productivity value got the highest value of 20.57, but in 2021 has the lowest value of 17.08. then it can be seen that the company has a business development strategy by relying on the quality of its products, in data processing with SWOT obtained internal and external variables are in quadrant 1 and the company must use the S-O strategy